2000
DOI: 10.1017/s0021900200015394
|View full text |Cite
|
Sign up to set email alerts
|

Poisson limits and nonparametric estimation for pairwise interaction point processes

Abstract: The distribution of the interpoint distance process of a sequence of pairwise interaction point processes is considered. It is shown that, if the interaction function is piecewise-continuous, then the sequence of interpoint distance processes converges weakly to an inhomogeneous Poisson process under certain sparseness conditions. Convergence of the expectation of the interpoint distance process to the mean of the limiting Poisson process is also established. This suggests a new nonparametric estimator for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The preceding proof appeals to [3,Theorem 2.3]. The hypotheses of that theorem are identical to those of our limit theorem, except for our extra assumption that be positive almost everywhere.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The preceding proof appeals to [3,Theorem 2.3]. The hypotheses of that theorem are identical to those of our limit theorem, except for our extra assumption that be positive almost everywhere.…”
Section: Discussionmentioning
confidence: 95%
“…The limit theorem of Appendix A shows that in the case of sparseness, the distribution of could be approximated by the distribution of the shot-noise random variable , and it is then shown that the distribution of could be computed using (6) or (12), depending on the form of the interaction function. While the analysis of (6) in Section IV-A is straightforward, the derivation of (12) in Section IV-B is more complicated, and the details are found in Appendix B. Extensions are treated in Appendix C. Finally, we note that our analysis of the sparseness conditions in Appendix D in the case of square regions leads to a simply computable value for the constant which appears in the characteristic function of in (5 (3) and (4)) and Now, the hypotheses of our theorem are sufficient for us to apply [3 …”
Section: Remarkmentioning
confidence: 93%
See 2 more Smart Citations
“…Due to the complex nature of the joint pdf of interaction point processes, exact performance analysis of hypothesis testing is generally intractable even in the simple case of the Strauss process. Monte Carlo simulation and approximation theory have been extensively used in estimating the performance of hypothesis testing problems involving interaction point processes [3], [9].…”
mentioning
confidence: 99%